Photoluminescence properties of ZnWO4: Dy 3+ phosphor - Dabre, K V; Dhoble, S J (Recent Research in Science and Technology, 2012)
Zinc tungstate (ZnWO4) exhibits interesting photoluminescent properties and ZnWO4 single crystal was first introduced for microwave devices, fiber optical communications, scintillating materials etc. In this paper reported the photoluminescence property of Dy3+ activated ZnWO4 synthesized by solid state rout at temperature 8500 C. Formation of compound was tested by X-ray diffraction pattern. The photoluminescence characteristic of Dy3+ doped ZnWO4 was studied by excitation and emission spectrum. PL excitation spectrum of ZnWO4:Dy3+ phosphor shows the broad excitation peaks ranging from 220 nm to 320 nm because of [WO6]6− group. The emission spectrum shows the peaks at 488 nm (blue) due to transition 4F9/2 →6H15/2 with broad background due to self emission of ZnWO4 and 575 nm (yellow) due to transition 4F9/2→ 6H13/2.